P155 Natural history of anal stricture in pediatric-onset Crohn's disease: a two-decades population-based study. (30th January 2023) - Mortreux, P; Leroyer, A; Ley, D; Dupont-Lucas, C; Bertrand, V; Wils, P; Coevoet, H; Paupard, T; Gower-Rousseau, C; Siproudhis, L; Guillon, N; Sarter, H; et al.
Abstract: Background: The natural history of anal stricture complicating pediatric-onset Crohn's disease (CD) is poorly known. The aims of this study were: to determine in a population-based study the risk of anal stricture in pediatric-onset CD; to identify risk factors for anal stricture; and to evaluate the natural history of anal stricture at the population level. Methods: All patients with a diagnosis of CD made before the age of 17 years between 1988 and 2011 in a population-based registry were followed retrospectively until 2013. A specific collection of additional data was performed in patients with anal stricture at diagnosis or during follow-up. Variables collected included: proctological examination, diagnostic management and treatment. Multivariate Cox models were used to identify factors associated with anal stricture. Results: Among the 1, 007 included CD patients (females, 451 (44.8%); median age at diagnosis 14.4 years (IQR, 12.0-16.1), median follow-up 8.8 years (IQR, 4.6-14.2)), only one (0.1%) had anal stricture at diagnosis while 26 (2.6%) presented anal stricture during follow-up. Cumulative incidence of anal stricture at 5 and 10 years after diagnosis was 0.6% (CI95%, 0.1-1.1) and 1.4% (CI95%, 0.5-2.3), respectively. Among the 27 patients with anal stricture, 25 (92.6%) had already at least one episode of anal ulceration or fistulizing perianal CD (pCD). In multivariable analysis, the presence of extra-intestinal manifestations (Hazard Ratio (HR) 2.2, CI95% 1.0-4.8, p=0.027), colonic location (L1 vs L3 HR 0.0 (-); L2 vs L3 HR 1.2, CI95% 0.6-2.7, p=0.006) and history of fistulizing pCD (HR 9.9, CI95% 4.3-22.8, p<0.0001) were significantly associated with anal stricture. Eleven (41%) patients needed at least one dilation. After a median follow-up of 16.9 years (IQR, 11.5-20.2), healing of anal stricture was observed only once. One patient (3.7%) presented an anal cancer 7 years after the diagnosis of anal stricture. Nine (33.3%) patients needed a stoma. Among them, 8 already had a fistulizing pCD and 4 needed an abdominoperineal amputation. Anal stricture was significantly associated with an increased risk of stoma (HR 5.8, CI95% 2.3-14.3), p=0.0002). Conclusion: Anal stricture is a rare event in pediatric onset CD, occurring in 1.5% of patients over a 10 year-period after diagnosis. However, anal stricture had a negative impact on disease prognosis with a five-fold increase of the risk of stoma.